PENGARUH PARTISIPASI MASYARAKAT TERHADAP IMPLEMENTASI KEBIJAKAN PEMBERDAYAAN DI DISTRIK SENTANI TIMUR KABUPATEN JAYAPURA - Situmorang, Elphyna (JURNAL EKOLOGI BIROKRASI, 2015)
Influence of Public Participation on Policy Implementation in the Eastern District of Sentani Empowerment Jayapura district. This study aims to: determine the level of community participation in the implementation of policies to support in the Eastern District of Sentani Jayapura district. This study took a sample of 200 respondents, sampling based on purposive sampling by category empowerment society actors in the district of East Sentani. The results showed that the implementation of the governments policy has been realized, however, there are still some obstacles that are non-technical. Society expects that the need for direct control of the government of the budgeting system in the villages through the Village Development Plan (RKPK) were prepared. The success of the implementation is influenced by several variables that became a benchmark of success, namely: community participation in planning (X1), community participation in the implementation of (X2), community participation in the use and maintenance of the results (X3), community participation in monitoring and evaluation (X4) , and community participation in the use of the opportunities of business activities (X5) and Policy Implementation Joint Product Development Program New Jayapura (Y). In implementations are positive and negative factors that can influence the course of development programs, in addition to some lack of success resulting from the application of the rules that have not been fully implemented. Keywords: Empowerment Program Policy